Is In-Stent Restenosis After a Successful Coronary Stent Implantation Due to Stable Angina Associated With TG/HDL-C Ratio?. (October 2017) - Kundi, Harun; Korkmaz, Ahmet; Balun, Ahmet; Cicekcioglu, Hulya; Kiziltunc, Emrullah; Gursel, Koray; Cetin, Mustafa; Ornek, Ender; Ileri, Mehmet
We examined the impact of the preprocedural triglyceride (TG)/high-density lipoprotein cholesterol (HDL-C) ratio on risk of in-stent restenosis (ISR). Patients with typical anginal symptoms and/or positive treadmill or myocardial perfusion scintigraphy test results who underwent successful coronary stent implantation due to stable angina were examined; 1341 patients were enrolled. The hospital files of the patients were used to gather data. Cox regression analysis showed that the TG/HDL-C ratio was independently associated with the presence of ISR ( P < .001). Moreover, diabetes mellitus ( P = .007), smaller stent diameter ( P = .046), and smoking status ( P = .001) were also independently associated with the presence of ISR. Using a cutoff of 3.8, the TG/HDL-C ratio predicted the presence of ISR with a sensitivity of 71% and a specificity of 68%. Also, the highest quartile of TG/HDL-C ratio had the highest rate of ISR ( P < .001). Measuring preprocedural TG/HDL-C ratio, in fasting or nonfasting samples, could be beneficial for the risk assessment of ISR. However, further large-scale prospective studies are required to establish the exact role of this simple, easily calculated, and reproducible parameter in the pathogenesis of ISR.